In the candidates' words: communication in social media during the 2018 Costa Rican electoral campaign - Carazo Barrantes, Carolina (2021)
Social media played an important role in the 2018 Costa Rican electoral contest: they were spaces to get informed, to participate in politics, and they were also platforms used by presidential candidates in their communication strategies. This article contributes to the analysis of the 2018 electoral campaign by considering a perspective so far absent in the discussion about communication and the role of social media in the electoral process: the presidential candidates´ opinions on the issues that marked the election. Seven candidates were interviewed. They spoke about social media in their campaign strategies, the part that television still plays, and citizen participation in the process; They also assessed the significance of WhatsApp usage during the contest, citizens' participation through massive groups on Facebook such as Coalición Costa Rica and Costa Rica Unida, and the problem of misinformation and false news. This article situates these opiniones within research on the election campaign.